Perceived human resource practices during Covid-19 pandemic: A study among tour guides in Kota Kinabalu, Malaysia - Datu Razali Datu Eranza; Shanan Navindra Shan Pillai; Lee, Andy Chen Hiung; Jabil Mapjabil; Siti Hasnah Tanalol; Arsiah Bahron (Academic Inspired Network (AIN), 2021)
COVID-19 has plunged global economy to recession and impacted businesses in all sectors, with reduction of manpower and termination of employment. Business organizations, especially those in the tourism industry may need to consider to continuously providing creative and innovative ways to support tour guides for personal development and self-enrichment. Support system like cost-effective training programme to tour guides can be meaningful and gain the affective commitment among the tour guides even post-termination. New approach in compensation, training and development, and performance appraisal would lead to a preparation for job performance in the future. The study has sampled 279 tour guides in Kota Kinabalu City, Sabah using online questionnaire, consists of questions related to human resource practices. The results suggested that all the practices studied have significant relationship to employee job performance especially during the difficult time of COVID-19 pandemic. The study recommends business firms to design an innovative and creative HR practices to support the tour guides regardless of the status of being employed or have been terminated. This may include facilitation of online training provided (free) by agencies and universities around the globe, financial aid and assistance programme by the Government, and facilitation of vaccination programme that could be very much meaningful to the tour guides.